Membangun Ketahanan Keuangan Keluarga Melalui Literasi Keuangan Di Desa Kotapulu - Siti Roziana; Farid Farid; Anisah Anisah (Cakrawala: Jurnal Pengabdian Masyarakat Global, 2023)
This activity aims to increase the understanding and knowledge of housewives in calculating and recording household cash receipts and disbursements properly so that there are no expenditures that are greater than income. So that the family's financial condition is always sufficient and has savings/investments for future needs, so that prosperity for the family is realized. The method used in this activity is by conducting discussions and coordination in advance with the village head and housewives. Participants take part in socialization with the classical method of providing material and followed by a question and answer session and practice/practice; presents a working paper that is filled according to the real conditions of the participants. The activity participants are housewives who do not work, housewives who work, and housewives who have their own business with an average educational background up to high school, as well as an economic background.